A multi-institutional review of endovenous thermal ablation of the saphenous vein finds male sex and use of anticoagulation are predictors of long-term failure. (May 2021) - Erben, Young; Vasquez, Isabel; Li, Yupeng; Gloviczki, Peter; Kalra, Manju; Oderich, Gustavo; De Martino, Randall R; Bjarnason, Haraldur; Neisen, Melissa J; Moore, January F; Da Rocha-Franco, Joao A; Sanchez-Valenzuela, Maria C; et al.
Background: To review long-term outcomes and saphenous vein (SV) occlusion rate after endovenous ablation (EVA) for symptomatic varicose veins. Methods: A review of our EVA database (1998–2018) with at least 3-years of clinical and sonographic follow-up. The primary end point was SV closure rate. Results: 542 limbs were evaluated. 358 limbs had radiofrequency and 323 limbs had laser ablations; 542 great saphenous veins (GSV), 106 small saphenous veins (SSV) and 33 anterior accessory saphenous veins (AASV) were treated. Follow-up was 5.6 ± 2.3 years; 508 (74.6%) veins were occluded, 53 (7.8%) partially occluded and 120 (17.6%) were patent. On multivariable Cox regression analysis, male sex (HR 1.6, 95% CI [0.46–018], p = 0.012) and use anticoagulation (HR 2.0, 95% CI [0.69–0.34], p = 0.044) were predictors of long-term failure. On Kaplan-Meier curve, we had an 86.3% occlusion rate. Conclusion: Our experience revealed a 5-year closure rate of 86.3%. Ablations have satisfactory occlusion rate.